PHYSIOLOGY OF EMBRYOS IN THE LAST INCUBATION PERIOD AND IN THE NUTRITION OF EGGS - Aslanova Muhtaram Askarovna (Journal of Medical Genetics and Clinical Biology, 2024)
One of the main physiological processes occurring during the pre-election period is the maintenance of glucose homeostasis. Glycogen stores are depleted as embryos hatch. The lack of glycogen causes the embryo to mobilize more muscle protein for gluconeogenesis, thereby slowing down early growth and development until glycogen stores begin to replenish when the newly hatched chick does not get full access to feed